Phosphoregulation of the Ceramide Transport Protein CERT at Serine 315 in the Interaction with VAMP-associated Protein (VAP) for Inter-organelle Trafficking of Ceramide in Mammalian Cells - Kumagai, Keigo (American Society for Biochemistry and Molecular Biology, 2014)
The ceramide transport protein CERT mediates the inter-organelle transport of ceramide for the synthesis of sphingomyelin, presumably through endoplasmic reticulum (ER)-Golgi membrane contact sites. CERT has a short peptide motif named FFAT, which associates with the ER-resident membrane protein VAP. We show that the phosphorylation of CERT at serine 315, which is adjacent to the FFAT motif, markedly enhanced the interaction of CERT with VAP. The phosphomimetic CERT S315E mutant exhibited higher activity to support the ER-to-Golgi transport of ceramide than the wild-type control in a semi-intact cell system, and this enhanced activity was abrogated when its FFAT motif was deleted. The level of phosphorylation of CERT at Ser-315 increased in HeLa cells treated with a sphingolipid biosynthesis inhibitor or exogenous sphingomyelinase. Expression of CERT S315E induced intracellular punctate structures, to which CERT and VAP were co-localized, and the occurrence of the structure was dependent on both phosphatidylinositol 4-monophosphate binding and VAP binding activities of CERT. Phosphorylation of another region (named a serine-rich motif) in CERT is known to down-regulate the activity of CERT. Analysis of various CERT mutant constructs showed that the de-phosphorylation of the serine-rich motif and the phosphorylation of Ser-315 likely have the additive contribution to enhance the activity of CERT. These results demonstrate that the phosphorylation of CERT at the FFAT motif-adjacent serine affected its affinity for VAP, which may regulate the inter-organelle trafficking of ceramide in response to the perturbation of cellular sphingomyelin and/or other sphingolipids.